Contextual role of architectural background images in digital comics - Anissa Febrina; Muhammad Heru Arie Edytia; Zia Faizurrahmany El Faridy (ARSNET, 2023)
This research aims to determine the role of architectural background images in digital comics and their proportional contribution to the overall reading interest. Digital comics are a form of media with sequential panels of images that project two-dimensional scenes positioned in a certain context. The context is presented in the background and is used as a story-building element in the comics. The study is interested in identifying important criteria of the architectural background as part of the digital comics narrative and measuring its relevance. This research uses the quantitative comparative method, with non-probability purposive sampling of 15 respondents. This research measured readers' interest in digital comics with and without an architectural background using a Likert scale and percentage interval scale to determine. Comparative analysis is done using two samples with the t-test. This research found that the percentage of readers' interest interval scale for digital comics with an architectural background is significantly higher in comparison with digital comics without an architectural background. The study demonstrates the various roles of architectural image as part of the story narrative, from clarification of the storyline and demonstrating representation of reality, to creating points of interest and focus.